PROKR2 mutations in idiopathic hypogonadotropic hypogonadism: selective disruption of the binding to a Gα‐protein leads to biased signaling. Issue 3 (21st December 2018) - Zhao, Yaguang; Wu, Jiayu; Jia, Hong; Wang, Xinying; Zheng, Ruizhi; Jiang, Fang; Chen, Dan-Na; Chen, Zhiheng; Li, Jia-Da
ABSTRACT: Idiopathic hypogonadotropic hypogonadism (IHH) is a rare disorder caused by the deficient production, secretion, or action of gonadotropin‐releasing hormone. Prokineticin (PROK) receptor 2 ( PROKR2 ), a causative gene for IHH, encodes a GPCR PROKR2. When PROKR2 binds to its ligands PROKs, it may activate several signaling pathways, including IP3/Ca 2+, MAPK, and cAMP pathways. However, the mutational spectrum of PROKR2 in Chinese patients with IHH has not been established. In the present study, we found that up to 13.3% (18/135) of patients with IHH in China carried mutations in PROKR2 . Most of the variants in this study were private; however, a PROKR2 (c.533G > C; p.W178S) mutation was identified in 10 independent patients, implying a possible founder mutation. Functional studies indicated that 6 novel PROKR2 mutations led to decreased signaling to various extents. Two IHH‐associated mutations (L218P and R270H) disrupted Gαq‐dependent signaling but maintained normal Gαs and ERK1/2 signaling. A glutathione S‐transferase pull‐down experiment demonstrated that R270H mutation disrupted the interaction of intracellular loop 3 of PROKR2 to Gαq protein but not Gαs protein. Our results indicated that selective disruption of the interaction with a specific Gα‐protein might underlie the biased signaling for certain IHH‐associated PROKR2 mutations.—Zhao, Y., Wu, J., Jia, H., Wang, X., Zheng, R., Jiang, F., Chen, D.‐N., Chen, Z., Li, J.‐D. PROKR2 mutations in idiopathic hypogonadotropic hypogonadism: selective disruption of the binding to a Gα‐protein leads to biased signaling. FASEB J. 33, 4538–4546 (2019). www.fasebj.org